Developing a Community-Based Productive Zakat Model for Socioeconomic Transformation of Mustahiq: Evidence from Kampung Zakat in Indonesia - Alfina Wildatul Fitriyah; Yasir Arafat; Halili; Wildan Miftahussurur; Dwi Rafelika Angger Adinata (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Productive zakat is increasingly recognized as a potential instrument for reducing poverty and promoting sustainable community empowerment. However, previous studies have largely emphasized economic outcomes, providing limited explanation of the integrated processes through which productive zakat supports long-term socioeconomic transformation. This study aims to develop an Integrated Community-Based Productive Zakat Model based on evidence from the Kampung Zakat program in Jember Regency, Indonesia. A qualitative case study design was employed. Data were obtained through semi-structured interviews, participant observation, and document analysis involving stakeholders and mustahiq directly engaged in the program. The data were analyzed inductively using the interactive framework of data condensation, data display, and conclusion drawing with continuous verification. The findings indicate that productive capital alone is insufficient to sustain beneficiaries' economic progress. Its effectiveness depends on its integration with entrepreneurship capacity building, continuous mentoring, spiritual development, community participation, and institutional collaboration. These interconnected elements form an empowerment ecosystem that strengthens productive capability, business resilience, social participation, self-confidence, and ethical responsibility, supporting the gradual movement of mustahiq toward greater economic independence and potential future contribution to community welfare. The study contributes to Islamic social finance literature by framing productive zakat as a multidimensional empowerment system rather than solely a redistributive mechanism. Practically, the proposed model offers guidance for zakat institutions and policymakers in designing more integrated and sustainable empowerment programs.